Towards National and Global Agendas: Latin America and the Caribbean - Berdegué, Julio A. (Washington, DC: World Bank, 2012)
A new agenda is needed to revitalize agriculture and rural areas of Latin America and the Caribbean (LAC) to improve overall development. The domestic market, in LAC and in most of its countries individually, is the largest and the fastest growing market for agricultural products, which creates important opportunities for agricultural growth. A strategy to promote small and medium family farms aimed at the new domestic markets should have the objectives of: (a) fostering an enabling environment for broad-based investment and growth, (b) developing and modernizing domestic markets to upgrade them to meet the challenge of new consumer demands and modern retail-driven food supply and distribution chains; and (c) strengthening the capacities of small and medium family farms through greater access to effective financial services, training, technical assistance and producers organizations.